Discovery and proteomics analysis of effective compounds in Valeriana jatamansi jones for the treatment of anxiety. (30th January 2021) - Wang, Shao-Nan; Yao, Zi-Wei; Zhao, Cheng-Bowen; Ding, Yong-Sheng; Jing-Luo,; Bian, Li-Hua; Li, Qiu-Yu; Wang, Xiao-Mei; Shi, Jin-Li; Guo, Jian-You; Wang, Chun-Guo
Abstract: Ethnopharmacological relevance: Zhizhu Xiang (ZZX for short) is the root and rhizome of Valeriana jatamansi Jones, which is a Traditional Chinese Medicine (TCM) used to treat various mood disorders for more than 2000 years, especially anxiety. However, there have been few investigations to clarify the compounds in ZZX for the treatment of anxiety. Aim of the study: Our previous study has identified five anti-anxiety components, including hesperidin, isochlorogenic acid A, isochlorogenic acid B and isochlorogenic acid C and chlorogenic acid, from extract of ZZX. In order to find the optimal combination and the underlying mechanism of these five components in the treatment of anxiety disorder, researches were designed based on uniform design method and proteomic technology. Materials and methods: The samples with different proportion and content of the five active components were arranged by uniform design method. Then a mathematical model was formulated using partial least square method and stepwise regression analysis. Moreover, the empty bottle stress-induced anxiety rat model was established, and the anti-anxiety effect was recorded by the unconditioned reflex elevated maze test and the open field test. In addition, the isobaric tags for relative and absolute quantitation (iTRAQ) technique, along with the multidimensional liquid chromatography and high-resolution mass spectrometry were applied in proteomic study. At last, the result of proteomic analysis was further confirmed by Western blot. Results: The optimal combination of the components from the extract of ZZX was 1.153 mg/kg hesperidin, 2.197 mg/kg Isochlorogenic acid A, 0.699 mg/kg Isochlorogenic acid B and 1.249 mg/kg Chlorogenic acid. Total 6818 proteins were identified using proteomic analysis and 80 differentially expressed proteins were used for further bioinformatic analysis. These proteins were involved in the neuroactive ligand-receptor interaction, protein digestion and absorption, cholesterol metabolism, Chagas disease, and AGE/RAGE signaling pathway. Conclusions: The composition and proportion of anti-anxiety components in extract of ZZX was disclosed, and there was an anti-anxiety effect for the combined components of flavonoids and phenolic acids. Through proteomic analysis and Western blot, it was found that the effective components of extract of ZZX can exert synergistic anti-anxiety effects via the regulation of multi-signaling pathways. These findings could provide a preliminary research basis for the development of new low-toxic, efficient, stable and controllable anti-anxiety drugs. Graphical abstract: Image 1 Highlights: The optimal combination of the antianxiety components in ZZX (the root and rhizome of Valeriana jatamansi Jones) was 1.153 mg/kg hesperidin, 2.197 mg/kg Isochlorogenic acid A, 0.699 mg/kg Isochlorogenic acid B and 1.249 mg/kg Chlorogenic acid. During the proteomic analysis, 80 proteins in rats were significantly influenced after dosing components mentioned above. Bioinformatic analyze results showed that the mechanism of ZZX-OS protect EBS rats from anxiety is related with the neuroactive ligand-receptor interaction, protein digestion and absorption, cholesterol metabolism, Chagas disease, and AGE/RAGE signaling pathway.